Depression Treatment and 1-Year Mortality After Acute Myocardial Infarction: Insights From the TRIUMPH Registry (Translational Research Investigating Underlying Disparities in Acute Myocardial Infarction Patients' Health Status). Issue 18 (2nd May 2017) - Smolderen, Kim G.; Buchanan, Donna M.; Gosch, Kensey; Whooley, Mary; Chan, Paul S.; Vaccarino, Viola; Parashar, Susmita; Shah, Amit J.; Ho, P. Michael; Spertus, John A.
Abstract : Background: Depression among patients with acute myocardial infarction (AMI) is prevalent and associated with an adverse quality of life and prognosis. Despite recommendations from some national organizations to screen for depression, it is unclear whether treatment of depression in patients with AMI is associated with better outcomes. We aimed to determine whether the prognosis of patients with treated versus untreated depression differs. Methods: The TRIUMPH study (Translational Research Investigating Underlying Disparities in Acute Myocardial Infarction Patients' Health Status) is an observational multicenter cohort study that enrolled 4062 patients aged ≥18 years with AMI between April 11, 2005, and December 31, 2008, from 24 US hospitals. Research coordinators administered the Patient Health Questionnaire-9 (PHQ-9) during the index AMI admission. Depression was defined by a PHQ-9 score of ≥10. Depression was categorized as treated if there was documentation of a discharge diagnosis, medication prescribed for depression, or referral for counseling, and as untreated if none of these 3 criteria was documented in the medical records despite a PHQ score ≥10. One-year mortality was compared between patients with AMI having: (1) no depression (PHQ-9<10; reference); (2) treated depression; and (3) untreated depression adjusting for demographics, AMI severity, and clinical factors. Results: Overall, 759 (18.7%) patients met PHQ-9 criteria for depression and 231 (30.4%) were treated. In comparison with 3303 patients without depression, the 231 patients with treated depression had 1-year mortality rates that were not different (6.1% versus 6.7%; adjusted hazard ratio, 1.12; 95% confidence interval, 0.63–1.99). In contrast, the 528 patients with untreated depression had higher 1-year mortality in comparison with patients without depression (10.8% versus 6.1%; adjusted hazard ratio, 1.91; 95% confidence interval, 1.39–2.62). Conclusions: Although depression in patients with AMI is associated with increased long-term mortality, this association may be confined to patients with untreated depression.